2016
DOI: 10.1007/s00277-016-2787-7
|View full text |Cite
|
Sign up to set email alerts
|

TERT rs2736100 genotypes are associated with differential risk of myeloproliferative neoplasms in Swedish and Chinese male patient populations

Abstract: The telomerase reverse transcriptase (TERT) gene rs2736100_C allele has recently been shown to be associated with an increased risk for myeloproliferative neoplasms (MPNs) among Caucasians. However, it is unknown if this association is present in other ethnical populations and whether rs2736100 allele frequencies mirror the incidence of MPNs in a population. Here we genotyped TERT rs2736100 variants in 126 Swedish and 101 Chinese MPN patients and their age-, sex-, and ethnically-matched healthy controls. Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…We found that the germline variants at the TERT locus significantly affected the TERT promoter mutation rate in HCC patients, and the TERT rs2736100-CC cancer risk genotype was more frequently seen in patients with a wt TERT promoter [65]. This variant is known to upregulate TERT expression, thereby counteracting telomere shortening [66].…”
Section: The Tert Gene and Its Promoter And Transcriptsmentioning
confidence: 93%
“…We found that the germline variants at the TERT locus significantly affected the TERT promoter mutation rate in HCC patients, and the TERT rs2736100-CC cancer risk genotype was more frequently seen in patients with a wt TERT promoter [65]. This variant is known to upregulate TERT expression, thereby counteracting telomere shortening [66].…”
Section: The Tert Gene and Its Promoter And Transcriptsmentioning
confidence: 93%
“…Wang et al [ 387 ] and Yang et al [ 388 ] published meta-analyses in which they reported the association of rs2736100 with increased lung cancer risk (mainly adenocarcinoma) in both Caucasian and Asian populations. This SNP was identified to associate with an increased risk of myeloproliferative neoplasms (e.g., polycythaemia vera, essential thrombocythemia, and primary myelofibrosis) in Caucasian and Chinese populations [ 267 , 269 ]. Conflicting results have been reported regarding the effect of this SNP on gastric cancer risk, in which rs2736100 was associated with increased risk in a Turkish population [ 265 ] but did not show impact on an Asian population, in which it correlated only with the regulation of TERT expression and telomere length [ 389 ].…”
Section: Telomere Maintenance Mechanismsmentioning
confidence: 99%
“…Indeed, by assessing leukocyte telomere length (LTL), many studies have shown that shorter LTL is associated with increased mortality, and ag-related diseases including cancer, cardiovascular disorders, stroke, diabetes, and among others [3,6]. In addition, certain genetic variants or single nucleotide polymorphisms (SNPs) at TERT and TERC genes, for instance, TERT rs2736100 and TERC rs12696304 have been shown to significantly impact telomere length by either up-regulating telomerase or other mechanisms, and in turn contribute to agerelated disorders [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Ivyspringmentioning
confidence: 99%
“…The TERC rs12696304(C/G) and TERT rs2736100 (A/C) genotyping was carried out using pre-designed TaqMan SNP genotyping assay kits on an ABI 7500 Life Tech (Applied Biosystems), as described [8,13]. Both positive and negative controls were included in all assays and PCR was run using the following conditions: 95°C for 5 min, followed by 40 cycles of 92°C for 15 s and 60°C for 30 s.…”
Section: Genotyping Of the Tert Rs2736100 And Terc Rs12696304 Variantsmentioning
confidence: 99%
See 1 more Smart Citation